IMPLEMENTASI STRATEGI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DP3A) DALAM MENEKAN PENINGKATAN ANGKA KEKERASAN SEKSUAL ANAK DI KABUPATEN TANGERANG, INDONESIA - Rahma Sita Dewi (Jurnal Anifa: Studi Gender dan Anak, 2022)
Child sexual violence there are still many cases of violence, namely as many as 72 victims of sexual violence against children. This study aims to determine the implementation of the Office of Women's Empowerment and Child Protection strategy in suppressing the increase in child sexual violence in Tangerang Regency. The research method used is descriptive qualitative research and analyzed by descriptive analysis. Based on the data analysis, it can be concluded that the implementation of strategies that can be carried out by the Office of Women's Empowerment and Child Protection in suppressing the increase in the number of child sexual violence in Tangerang Regency is by analyzing programs, budgets, and procedures. The first program is several PATBM in the village or village has not been running. Secondly, advocacy socialization through BK/BP teachers has been given socialization by service to BK/BP teachers, but only part of the socialization has not been right on target, namely all students. Third, socialization to the community through community leaders where community leaders have never received directions from the department or village. The budget still has its budget limitations. There are still programs or activities whose implementation has not been to the plan due to budget limitations. In the implementation of Standard Operating Procedures (SOP), some problems are still victims of violence who are less cooperative in handling cases of child sexual violence.